а) 3Х^2-12Х = 3Х(Х-4)
б) ав-2а+в^2-2в = (ав-2а)+(в^2-2в) = а(в-2)+в(в-2) = (а+в)(в-2)
в) х^3-8х^2+16х = х(х^2-8х+16)-это формула сокращенного умножения=х(х-4)^2 скобка в квадрате=х(х-4)(х-4)
а)
б)
или
в)
а) 3Х^2-12Х = 3Х(Х-4)
б) ав-2а+в^2-2в = (ав-2а)+(в^2-2в) = а(в-2)+в(в-2) = (а+в)(в-2)
в) х^3-8х^2+16х = х(х^2-8х+16)-это формула сокращенного умножения=х(х-4)^2 скобка в квадрате=х(х-4)(х-4)
а)![3x^{2}-12x=3x(x-4)](/tpl/images/0055/7307/c0a8f.png)
б)![ab-2a+b^{2}-2b=(ab-2a)+(b^{2}-2b)=a(b-2)+b(b-2)=(b-2)(a+b)](/tpl/images/0055/7307/2c66c.png)
или
в)![x^{3}-8x^{2}+16x=x(x^{2}-8x+16)=x(x-4)^{2}=x(x-4)(x-4)](/tpl/images/0055/7307/3a2de.png)
или